The Woman with the Flow of Blood in the Homily of Pseudo-Chrysostom and the Kontakion of Romanos the Melodist - Dźwigała, Katarzyna Maria (Verbum Vitae, 2020)
The piece considers the story of the woman with the flow of blood (haimorrhoousa) in the Gospels of Matthew, Mark, and Luke as it is represented in two works: the homily of Pseudo-Chrysostom (PG 59,575-578) and Kontakion 12 (in the Oxford edition) of Romanos the Melodist. Interpretations of this episode from the gospels touch upon the issue of ritual purity in the Jewish law as well as the attitude of Christian authors toward female menstruation. The texts mentioned above are examined, along with statements from the Fathers of the Church on menstruation, in an attempt to answer the question of whether Christian authors embraced the idea that menstruating women should be excluded from social and religious life. The article shows that the attitude of Christian authors towards menstruating women was in fact generally positive.